2017
DOI: 10.1016/j.molimm.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature structure of human IgG4-Fc from crystals analysed in situ

Abstract: HighlightsRoom temperature structure of human IgG4-Fc solved from crystals analysed in situ.Structure reveals changes in crystal packing at different temperatures.Structure reveals physiologically relevant conformation of a key Fcγ receptor binding loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Evidence suggests that FAE and Fc-Fc reactivity may involve the same molecular structure on IgG4 molecule. 10 Davies et al 11 12 resolved the crystal structure of IgG4 Fc fragment revealing a unique molecular conformation supporting its Fc binding property. Recent interests in IgG4-related diseases unveiled a wide range of pathologies with a common phenomenon of often increased IgG4 concentration in the serum and IgG4-postive plasma cells in the affected organs accompanied by local inflammation and fibrosis, but its pathogenic mechanism is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that FAE and Fc-Fc reactivity may involve the same molecular structure on IgG4 molecule. 10 Davies et al 11 12 resolved the crystal structure of IgG4 Fc fragment revealing a unique molecular conformation supporting its Fc binding property. Recent interests in IgG4-related diseases unveiled a wide range of pathologies with a common phenomenon of often increased IgG4 concentration in the serum and IgG4-postive plasma cells in the affected organs accompanied by local inflammation and fibrosis, but its pathogenic mechanism is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…As a different perspective altogether, one previous structural study of the full-length IgG4 antibody suggested that the IgG4 glycans may not reside in the internal cavity of the Fc subunit, as shown in Fig 1B, but are solvent exposed [12]. That study attributed this outcome to the shorter IgG4 hinge that forced the C H 2 domains into an unorthodox conformation that differed from the available IgG4-Fc crystal structures [14][15][16]. Such a C H 2 domain rearrangement may itself reduce IgG4 function because the contact residues for FcγR and C1q binding have been displaced, however this appears unlikely.…”
Section: Plos Onementioning
confidence: 90%
“…Two detailed crystal structures for full length IgG4 (PDB ID: 5D43 and 6GFE) [12,13] provide only a single view of the IgG4 structure and not the full conformational space that the Fc and Fab subunits can occupy in solution. Six glycosylated IgG4 Fc crystal structures showed the glycans facing inward within the C H 2 domains (PDB ID: 4C54, 4C55, 5LG1, 5W5M and 5W5N) [14][15][16]. One high-resolution structure of a deglycosylated IgG4-Fc (PDB ID: 4D2N) showed that the C H 2-C H 2 domain interactions bury in part the C H 2 surface that would be solvent exposed with the glycan present [17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate a role of electron transfer from Tyr to Trp +· for the initiation of Tyr side chain cleavage, we inspected the crystal structure of IgG4-Fc (PDB 4C54). , The structure revealed three Trp residues located adjacent to Tyr 373 , Tyr 436 , and Tyr 300 , respectively, displayed in Figure . Trp 313 is located 11.3 Å from Tyr 373 , Trp 381 is located 12.1 Å from Tyr 436 , and Trp 313 is located 18.1 Å from Tyr 300 .…”
Section: Discussionmentioning
confidence: 99%